FACTORS INFLUENCING VEGETABLE AND FRUITS CONSUMPTION BEHAVIOR IN EARLY CHILDREN KINDERGARTEN WORKING AREA OF THE RI SIDOMULYO PUSKESMAS - Alhidayati Alhidayati; Jihan Natassa; Christine Vita Gloria Purba; Mursydah Dewi (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2023)
Consumption of vegetables and fruits that contain sources of vitamins, minerals and fiber are needed by the body in achieving a healthy lifestyle. Consuming less vegetables and fruit can cause degenerative diseases such as obesity, diabetes, hypertension, high blood pressure, and cancer. Riskesdas 2018 data states that as many as 95.5% of the population aged ≥5 years consume vegetables and fruits under the recommendation. The purpose of this study was to determine the factors that influence fruit and vegetable consumption in early childhood kindergartens in the working area of ​​the RI Sidomulyo puskesmas. The research is quantitative with cross sectional design. The sampling technique uses stratified random sampling technique with a sample of 99 people. Statistical test results using Chi square obtained knowledge of mother's nutritional P value = 0.373> α 0.05 (CI = 649-3.164), children's nutritional status P value = 0.903> α 0.05 (CI = 385-4436), Children's Favorite P value = 0.050 <α 0.05 (CI = 1,103-8,233), Availability of Vegetables and Fruits P value = 0.023 <α 0.05 (CI = 1,226-6,302), Menu Variations P value = 0,600> α 0.05 (CI = 514-3,160), Family Practice P value = 0.814> α 0.05 (CI = 0.401-2.051), Family Income P value = 0.070 <α 0.05 (CI = 683-54.007). The conclusion is that there is no relationship between maternal nutritional knowledge, nutritional status, variations in menu, family practices while preference, availability of vegetables and fruit, family income is related to the behavior of kindergarten consumption of fruits and vegetables in the working area of ​​the RI Sidomulyo Puskesmas in 2020. It is expected that the puskesmas and schools to be able to provide parents with information about the importance of vegetable and fruit consumption so that they can prepare vegetables and fruit for their children's daily supplies.